CULTURAL HEGEMONY OF VOICE OF AMERICA (VOA) IN PROGRAM VOA GONDANGDIA (THANKSGIVING EPISODE) ON INDONESIAN DANGDUT RADIO - Revi Swandarini; Deavvy M.R.Y Johassan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Radio is one form of mass media that is quite easily accessible by anyone. The broadcast programs owned by Radio Dangdut Indonesia are quite diverse. Radio Dangdut Indonesia believes that all its programs are prime time. However, there is one program that according to the author is quite unique, namely VOA GONDANGDIA which incidentally is an acronym for